Network Simulation Using Cisco Packet Tracer in Computer Network Learning in Higher Education - Steven J Runtuwene; Adinda N. Abdulgani; Octhanine M. L. Pakan; Friendly C. G. Pinontoan; Daniel I. Mangaronda; Trivena N. Kambey (Jurnal Syntax Admiration, 2024)
The development of computer network technology is growing day by day. Therefore, understanding computer networks is part of the competencies that students in higher education must have. Informatics engineering and computer science are study programs at universities that always study computer networks. One effective teaching method in network learning is to carry out network simulations using Cisco Packet Tracer. This method can help students to interactively understand all aspects of the network without requiring expensive hardware. This research discusses the use of Cisco Packet Tracer in the computer network learning process in higher education. Based on research results, Cisco Packet Tracer is related to increasing students' understanding of network design and configuration. In addition, the use of simulations simplifies the learning process and reduces the costs of the facilities required.